2017
DOI: 10.3390/s17040815
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Streaming Mass Spatio-Temporal Vehicle Data Access in Urban Sensor Networks Based on Apache Storm

Abstract: The efficient data access of streaming vehicle data is the foundation of analyzing, using and mining vehicle data in smart cities, which is an approach to understand traffic environments. However, the number of vehicles in urban cities has grown rapidly, reaching hundreds of thousands in number. Accessing the mass streaming data of vehicles is hard and takes a long time due to limited computation capability and backward modes. We propose an efficient streaming spatio-temporal data access based on Apache Storm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Previous studies showed significant advantages from the integration of big data technologies such as reducing the processing time for home automation systems [ 38 ], providing effective and efficient solutions for processing IoT-generated data for smart cities [ 39 ], and handling large amounts of smart environmental data in real-time [ 40 ]. The aforementioned big data technologies have been integrated in data processing systems, resulting in significant advantages due to processing large amounts of streaming spatiotemporal data [ 41 ] as well as processing massive amounts of manufacturing sensor data efficiently [ 42 ]. Therefore, it is necessary to integrate Apache Kafka, Apache Storm, and MongoDB in big data processing systems for the manufacturing industry so that large amounts of streaming manufacturing sensor data can be promptly processed, stored, and presented in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed significant advantages from the integration of big data technologies such as reducing the processing time for home automation systems [ 38 ], providing effective and efficient solutions for processing IoT-generated data for smart cities [ 39 ], and handling large amounts of smart environmental data in real-time [ 40 ]. The aforementioned big data technologies have been integrated in data processing systems, resulting in significant advantages due to processing large amounts of streaming spatiotemporal data [ 41 ] as well as processing massive amounts of manufacturing sensor data efficiently [ 42 ]. Therefore, it is necessary to integrate Apache Kafka, Apache Storm, and MongoDB in big data processing systems for the manufacturing industry so that large amounts of streaming manufacturing sensor data can be promptly processed, stored, and presented in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [12] propose a system for efficient streaming access and cleaning of spatiotemporal data, which is also based on Apache Storm. It uses Apache Kafka, a distributed, partitioned, replicated commit log service in order to integrate the data into the Storm cluster.…”
Section: Related Workmentioning
confidence: 99%
“…Since Spark has outstanding processing capabilities for massive real-time data, Spark has attracted greater attention among developers. Meanwhile, the current trend is to use real-time computation technologies in a GIS [27]. Therefore, Spark also supports real-time and open GIS.…”
Section: Introductionmentioning
confidence: 99%